Interactive cd to reinforce english reading Skill in students of first year bachillerato at unidad educativa La Libertad, La Libertad, province of Santa Elena. School year 20142015. - Reyes Suárez, Carlos Efraín (2016)
This research project elaborated and implemented an Interactive Reading CD with the objective to improve English reading skill in students of first year of Bachillerato at Unidad Educativa La Libertad, its design was supported by the use and application of the ICT in Education. For the development of the research was necessary to apply surveys and interviews to the principal of the institution and a specialist in technology. Also a diagnostic test was taken in order to measure the level of reading in students, throughout the implementation of the proposal students developed some reading activities and practiced their comprehension, the proposal also has the option to listen audio scripts of the readings. Results showed that students improved their reading skill such as comprehension, pronunciation, fluency, punctuation and vocabulary afterward the implementation of the Interactive Reading CD, in consequence this project is recommended for the Unidad Educativa La Libertad as a tool to improve the teaching-learning process in response to the demands of new generations.